CORRELATION OF NATURAL PULSED ELECTROMAGNETIC FIELD OF THE EARTH WITH STRESSES AND DEFORMATIONS, WHICH APPEARED IN EXHAUSTED SALT FIELDS IN THE PRECARPATHIANS FOR KARST CREATION FORECASTING - Bagriy, S.; Kuzmenko, E.; Dzoba, U. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem of solving the ecological and geological issues which arise as the result of working off in natural resources (in particular the deposits of potassium salts) is actual at this time. Specificity is in easy solubility of salts and therefore the creation of artificial cavities and karstic phenomena. The article examines the ways to solve the problems of mapping the salt karst and forecasting creation of dips and subsidence of the earth’s surface by the example of Kalush-Holyn potassium salt deposit which is located in Ukrainian Precarpathians. As the basis of the research, the complex geophysical methods were considered. It was proved that the method of natural pulsed electromagnetic field of the Earth (NPEMFE) can be selected as a reliable evaluation method of stress-strain state of rocks and prediction of karst processes and deformations which is associated with the presence of extracting chambers. The article describes the physical preconditions for applying the method, sets out the basic postulates of field intensity anomalies classification and proposes the methodology for depth evaluation. Using the real examples - the profile and planar research of potassium salt deposit - the succes of the NPEMFE method is shown, along with its effectiveness to solve some ecological and geological problems, as well as feasibility of using the method in other areas.